Design, Synthesis, and Biological Evaluation of C-2 Substituted 3Hthieno[ 2,3-d]pyrimidin-4-one Derivatives as Novel FGFR1 Inhibitors - Guo, Ping; Xie, Zixin; Zhang, Huan; Zhang, Zaikui; Han, Chao; Cheng, Donghua; Lin, Dan; Zhang, Yuan; Wang, Xuebao; Guo, Xin; Ye, Faqing (Medicinal Chemistry, 2017)
Background: Thienopyrimidinone is a newly designed, selective fibroblast growth factor receptor 1 (FGFR1) inhibitor with an excellent anticancer effect. Objective: The goal of the present study was to design and synthesize better FGFR1 inhibitors through modifications of the lead compound thienopyrimidinone. Methods: In the present study, a series of C-2 substituted derivatives of thienopyrimidinone, namely L1-L16, were synthesized, and their inhibitory effects on FGFR1 were evaluated. The anti-proliferative activities of these compounds were assessed by MTT assay. Results: Among the novel derivatives, L11 was found to exert remarkable FGFR1 inhibitory activity (79.93% at 10 μM) and anti-proliferative activity, with IC50 values of 2.1, 2.5, and 3.5 µM in the FGFR1-overexpressing cell lines, H460, HT-1197, and B16F10, respectively. Conclusion: Our newly synthesized thienopyrimidinone derivatives may be candidate FGFR1 inhibitors for future development as novel anticancer agents.
Keywords: FGFR1